A Nortriterpenoid and Steroid from the Stem Bark of Aglaia angustifolia Miq (Meliaceae) - Ricson Pemimpin Hutagaol; Unang Supratman; Ihsan Rahadian; Srikandi Srikandi; Desi Harneti; Ace Tatang Hidayat; Khalijah Awang; Yoshihito shiono (Syarif Hidayatullah State Islamic University, 2022)
A nortriterpenoid, 3-epi-cabraleahydroxylactone (1) and a steroid, stigma-4-en-3-on (2) were isolated from the n-hexane extract of stem bark of Aglaia angustifolia Miq. Compound (2) was isolated for the first time from this Genus. The structure of both compounds were identified by spectroscopic datas including one and two-dimensional NMR as well as infrared spectrum, high-resolution mass spectrometric analysis and by comparing with those spectral data previously.